Demon dentist - Walliams, David 1971- (HarperCollins Children's Books, 2015)
Darkness had come to the town. Strange things were happening in the dead of night. Children would put a tooth under their pillow for the tooth fairy, but in the morning they would wake up to find ... a dead slug ; a live spider ; hundreds of earwigs. Evil was at work, but who or what was behind it?